Charting new directions for muslim universities - Zakariya, Hafiz (Institut Penyelidikan Pendidikan Tinggi Negara (IPPTN), USM, 2012)
This collaborative work examines various aspects of higher education in Muslim countries. Topics range from the philosophical, structural dimensions and reforms in teaching and learning as well as alternative ranking system.